Pengaruh Penggunaan Media Pop Up Book terhadap Pemahaman Konsep IPAS Siswa Kelas IV SDN 28 Cakranegara - Devina Anggraini; Sudirman; Nurkhaerat Alimuddin (Mataram University, 2026)
Conceptual understanding is a crucial skill for students in IPAS (Natural and Social Sciences) learning. However, because the learning process is still dominated by the use of unengaging media, students' conceptual understanding remains suboptimal therefore, innovative and interactive learning media such as pop up books are needed. This study aimed to determine the effect of using Pop-Up Book media on fourth-grade students’ understanding of IPAS concepts on plant parts material at SDN 28 Cakranegara in the 2025/2026 academic year. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research was conducted at SDN 28 Cakranegara. The subjects consisted of 60 fourth-grade students, including 30 students from Class IV A as the control group and 30 students from Class IV B as the experimental group. The research data were primary data obtained from students’ pretest and posttest scores on concept understanding. Data were collected through tests and observations. The research instrument was a multiple-choice test that had been tested for validity using Pearson Product Moment Correlation and reliability using Cronbach’s Alpha. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s Test of Homogeneity, and the Independent Samples t-Test with the assistance of IBM SPSS Statistics 32. The results showed that the data were normally distributed and homogeneous. The hypothesis testing revealed a significance value of 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. The mean posttest score of the experimental group was 8.67, which was higher than that of the control group at 7.17. Therefore, the use of Pop-Up Book media had a significant effect on fourth-grade students’ understanding of IPAS concepts on plant parts material at SDN 28 Cakranegara. Based on these findings, teachers are recommended to use Pop-Up Book media as an alternative instructional medium to improve students’ conceptual understanding in IPAS learning.